Penerapan Metode Trend Moment Dalam Sistem Forecasting Untuk Memprediksi Jumlah Penjualan Smartphone dan Aksesoris - Kevin Louis; Christina Julia Sinaga; Putra Edi Mujahid (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Trend Moment and Forecasting are data retrieval methods that have accurate and effective suitability to handle problems such as large amounts of data. The Trend Moment method is an approach that uses special statistical and mathematical calculation techniques to replace broken lines formed from the company's historical data with a straight line function. The Star Communicator store is one of the stores in the city of Medan that is engaged in selling various brands of smartphones and their accessories. Currently, the Star Communicator store still uses a conventional system to record its sales data. The admin staff will record product sales data. Then, at the end of the month, a sales recapitulation will be made to the store owner. The implementation of this system has a weakness where the company owner cannot know which products are more in demand by customers in a certain period. This information is needed so that the company owner can control smartphone stock in the company. Therefore, it is necessary to apply a smartphone prediction system. The result of this research is a desktop application that can be used to predict the number of smartphone sales in a certain period. From the results of the tests carried out, information was obtained that the average level of accuracy of the Trend Moment method was 70.22%. This means that the level of accuracy of the prediction results from the Trend Moment method is still not good. To improve the accuracy of the prediction results, the Trend Moment method can be combined with other methods, such as the Linear Regression method. In addition, other supporting factors for predictions can also be added, such as holiday factors or certain holidays which are often known as the holiday effect.